2003
DOI: 10.1073/pnas.2034960100
|View full text |Cite
|
Sign up to set email alerts
|

Interference with T cell receptor–HLA-DR interactions by Epstein–Barr virus gp42 results in reduced T helper cell recognition

Abstract: Epstein-Barr virus (EBV) persists lifelong in infected hosts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 44 publications
1
103
0
1
Order By: Relevance
“…Therefore, the dramatic reduction in total TLR9 protein levels in lytically infected cells, combined with metabolic labeling experiments showing TLR9 protein to have stability similar to that of the TfR, raise the prospect that EBV also targets TLR9 posttranslationally. The existence of viral strategies other than host shutoff targeting TLR9 would provide an intriguing parallel to EBV-mediated subversion of adaptive Ag presentation pathways: BNLF2a and BILF1 combine with BGLF5 to sabotage HLA class I Ag presentation (35,39), whereas gp42 complements the effect of BGLF5 on HLA class II-restricted T cell recognition (28,40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dramatic reduction in total TLR9 protein levels in lytically infected cells, combined with metabolic labeling experiments showing TLR9 protein to have stability similar to that of the TfR, raise the prospect that EBV also targets TLR9 posttranslationally. The existence of viral strategies other than host shutoff targeting TLR9 would provide an intriguing parallel to EBV-mediated subversion of adaptive Ag presentation pathways: BNLF2a and BILF1 combine with BGLF5 to sabotage HLA class I Ag presentation (35,39), whereas gp42 complements the effect of BGLF5 on HLA class II-restricted T cell recognition (28,40).…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus 16 E5 protein perturbs MHC class II maturation by inhibiting the degradation of invariant chain (32). EBV gp42 impairs T cell activation by binding to HLA class II molecules and blocking TCR engagement (33). Lymphocytic choriomeningitis virus interferes with DC maturation and Ag-presenting activity by reducing the surface expression of MHC class I, MHC class II, CD40, CD80, and CD86 molecules (42).…”
Section: Discussionmentioning
confidence: 99%
“…The following Abs have been used in this study and, unless otherwise indicated, were described elsewhere (19,(25)(26)(27). OX34 (American Tissue Culture Collection) is a mouse IgG2a mAb specific for the extracellular domain of rat CD2.…”
Section: Antibodiesmentioning
confidence: 99%
“…SDS-PAGE and immunoblotting were performed as reported previously (19). Briefly, total postnuclear Nonidet P-40 cell lysates were denatured in reducing sample buffer (final concentration: 2% SDS, 50 mM Tris-HCl, pH 8.0, 10% glycerol, 5% 2-ME, 0.05% bromphenol blue) and solubilized proteins equivalent to 2 ϫ 10 5 cells were separated by 10% SDS-PAGE and transferred to polyvinylidene difluoride membranes (Amersham Biosciences).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation